Nanopeptide C-I20 as a novel feed additive effectively alleviates detrimental impacts of soybean meal on mandarin fish by improving the intestinal mucosal barrier - Huo, Xingchen; Zhang, Qiwei; Chang, Jiao; Yang, Gang; He, Shan; Yang, Chunrong; Liang, Xufang; Zhang, Yongan; Su, Jianguo (Frontiers in Immunology, 2023)
Antibacterial peptide has been widely developed in cultivation industry as feed additives. However, its functions in reducing the detrimental impacts of soybean meal (SM) remain unknown. In this study, we prepared nano antibacterial peptide CMCS-gcIFN-20H (C-I20) with excellent sustained-release and anti-enzymolysis, and fed mandarin fish (Siniperca chuatsi) with a SM diet supplemented with different levels of C-I20 (320, 160, 80, 40, 0 mg/Kg) for 10 weeks. 160 mg/Kg C-I20 treatment significantly improved the final body weight, weight gain rate and crude protein content of mandarin fish and reduced feed conversion ratio. 160 mg/Kg C-I20-fed fish maintained appropriate goblet cells number and mucin thickness, as well as improved villus length, intestinal cross-sectional area. Based on these advantageous physiological changes, 160 mg/Kg C-I20 treatment effectively reduced multi-type tissue (liver, trunk kidney, head kidney and spleen) injury. The addition of C-I20 did not change the muscle composition and muscle amino acids composition. Interestingly, dietary 160 mg/Kg C-I20 supplementation prevented the reduction in myofiber diameter and change in muscle texture, and effectively increased polyunsaturated fatty acids (especially DHA + EPA) in muscle. In conclusion, dietary C-I20 in a reasonable concentration supplementation effectively alleviates the negative effects of SM by improving the intestinal mucosal barrier. The application of nanopeptide C-I20 is a prospectively novel strategy for promoting aquaculture development.